2020
DOI: 10.1007/s10494-020-00171-9
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Turbulence and Temperature Fluctuations on Knock Development in an Ethanol/Air Mixture

Abstract: The effects of turbulence on knock development and intensity for a thermally inhomogeneous stoichiometric ethanol/air mixture at a representative end-gas autoignition condition in internal combustion engines are investigated using direct numerical simulations with a skeletal reaction mechanism. Two-and three-dimensional simulations are performed by varying the most energetic length scale of temperature, l T , and its relative ratio with the most energetic length scale of turbulence, l T ∕l e , together with tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…The KAUST Adaptive Reacting Flow Solver (KARFS) [2,3,41,49] is used to solves the fully compressible Navier-Stokes, species and energy equations for gaseous mixtures. An eighth-order finite-difference scheme was employed for the spatial discretization of the diffusive terms.…”
Section: Numerical Methods and Initial Conditionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The KAUST Adaptive Reacting Flow Solver (KARFS) [2,3,41,49] is used to solves the fully compressible Navier-Stokes, species and energy equations for gaseous mixtures. An eighth-order finite-difference scheme was employed for the spatial discretization of the diffusive terms.…”
Section: Numerical Methods and Initial Conditionsmentioning
confidence: 99%
“…Modern internal combustion (IC) engines operate under elevated pressure enabled by downsized boosted technologies to achieve higher thermal efficiency, higher power-density output per volume, and ultra-low emission. However, being operated at elevated pressure and high-load conditions leads to a higher propensity of undesired preignition, knock, and even superknock [1][2][3][4][5][6][7][8]. Superknock is characterized as a developing detonation process featuring excessive pressure oscillations and extremely high-pressure amplitudes that can damage combustion-chamber components [7,[9][10][11][12][13][14][15][16][17][18][19][20]20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Luong et al [13] used two-dimensional (2D) and threedimensional (3D) DNS to study the effects of turbulence on knock characteristics using a stoichiometric ethanol/air mixture. They found that once the most energetic length scale associated with the fluctuation of temperature or velocity starts to increase, the detonation becomes more likely, because this allows a larger distance for detonation to develop.…”
Section: Introductionmentioning
confidence: 99%